UTILIZING DIGITAL TECHNOLOGY IN INDONESIAN LANGUAGE EDUCATION TO ENHANCE STUDENTS' ABILITY TO COMPOSE EXPOSITORY TEXTS - Mastawati Ndruru (Universitas Nias Raya, 2025)
This study aims to examine the utilization of digital technology in Indonesian language learning to improve students' ability to compose expository texts. Expository text writing is an important skill in Indonesian language learning that involves the ability to organize ideas, information, and arguments in a systematic and structured manner. However, many students face difficulties in composing expository texts due to a lack of understanding of the correct structure and language rules. Digital technology, with its various applications and e-learning platforms, offers a solution to facilitate more interactive and engaging learning. This study uses a qualitative method with a case study approach to explore the application of digital technology in expository text learning at schools. The research findings indicate that the use of digital technology, such as writing applications, collaborative platforms, and tutorial videos, can enhance students' understanding of expository text structure and improve their writing skills. This study is expected to provide new insights for educators to integrate digital technology more effectively in Indonesian language learning, especially in the teaching of expository texts.